2018
DOI: 10.1017/s0950268818001851
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis surveillance by small serosurveys of blood donors

Abstract: Serosurveys have established data about the distribution of immunoglobulin G (IgG)-antibodies to pertussis toxin (PT) in various populations. We tried to detect whether small serosurveys in blood donors could serve as a simple and inexpensive means to collect information about the circulation of Bordetella pertussis. We screened every donation in 307 adult blood donors aged 19-69 years for IgG-anti-PT by standardised enzyme-linked immunosorbent assays (ELISA), and the donors were followed between 2014 and 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…A nationwide seroprevalence in a wider age range is suggested for better assessment of the magnitude of exposure and impact of vaccination interventions as well. However, seroepidemiological surveys of blood donors 47 and high-risk occupational groups (eg, HCWs and military personnel) may provide a more feasible and realistic estimate of pertussis infection. Immunity from infection or vaccination with pertussis is not permanent, 48 and the high circulation of this pathogen represents a threat to the most susceptible populations (ie, infants and the elderly).…”
Section: Discussionmentioning
confidence: 99%
“…A nationwide seroprevalence in a wider age range is suggested for better assessment of the magnitude of exposure and impact of vaccination interventions as well. However, seroepidemiological surveys of blood donors 47 and high-risk occupational groups (eg, HCWs and military personnel) may provide a more feasible and realistic estimate of pertussis infection. Immunity from infection or vaccination with pertussis is not permanent, 48 and the high circulation of this pathogen represents a threat to the most susceptible populations (ie, infants and the elderly).…”
Section: Discussionmentioning
confidence: 99%
“…Demographic characteristics including age, gender, sibling under 5 years and history of long-lasting cough were not significantly associated with serology rates ( P > 0.05). Varied results have been described elsewhere [ 13 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to the persisting vaccine-acquired immunity, that still be observed within 3 years from the last vaccination dose [ 18 , 21 ]. Increased anti-PT IgG levels have been observed in countries using the acellular vaccine, including the Netherlands [ 22 ] and Germany [ 13 ]. Moreover, it has been reported that DTwP primed-children are better protected against pertussis than DTaP primed adolescents [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of anti-PT IgG (IU/ml) is a marker of either pertussis infection or vaccination and is specific for B. pertussis [20][21][22]. The presence of anti-PT IgG was detected by quantitative analysis using a commercially available ELISA kit (EUROIMMUN, Lübeck, Germany).…”
Section: Laboratory Methodsmentioning
confidence: 99%